Diluted magnetic А₁₋xMnxВ semiconductors - Bryksa, V.P.; Tarasov, G.G.; Masselink, W.T.; Nolting, W.; Mazur, Yu.I.; Salamo, G.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Novel model of the diluted magnetic semiconductors (DMS) А₁₋xMnxВ possessing the
metallic conductivity is proposed. Using the coherent potential technique the electron scattering
by the randomly distributed Mn centers is taken into account. The exchange scattering of the
electron spin by the localized magnetic mo exactly basing on the
spin-polaron limit for the Vonsovskii Hamiltonian.